Respuesta :

Answer:answer is a (x+8)^2=86

Step-by-step explanation:

x+8=±√

​86

​​

2 Break down the problem into these 2 equations.

x+8=\sqrt{86}x+8=√

​86

​​

x+8=-\sqrt{86}x+8=−√

​86

​​

3 Solve the 1st equation: x+8=\sqrt{86}x+8=√

​86

​​ .

x=\sqrt{86}-8x=√

​86

​​ −8

4 Solve the 2nd equation: x+8=-\sqrt{86}x+8=−√

​86

​​ .

x=-\sqrt{86}-8x=−√

​86

​​ −8

5 Collect all solutions.

x=\sqrt{86}-8,-\sqrt{86}-8x=√

​86

​​ −8,−√

​86

​​ −8

x

​2

​​ +16x−22=0

2 Use the Quadratic Formula.

x=\frac{-16+2\sqrt{86}}{2},\frac{-16-2\sqrt{86}}{2}x=

​2

​−16+2√

​86

​​

​​ ,

​2

​−16−2√

​86

​​

​​

3 Simplify solutions.

x=-8+\sqrt{86},-8-\sqrt{86}x=−8+√

​86

​​ ,−8−√

​86

​​

The equivalent equation x² + 16x = 22 will be (x + 8)² = 86. Then the correct option is A.

What is an equivalent expression?

The equivalent is the expressions that are in different forms but are equal to the same value.

The equation is given below.

x² + 16x = 22

Add both side 64.

x² + 16x + 64 = 22 + 64

         (x + 8)² = 86

Then the correct option is A.

More about the equivalent link is given below.

https://brainly.com/question/889935

#SPJ5